1996
DOI: 10.1002/(sici)1097-4547(19960501)44:3<216::aid-jnr2>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐astrocytoma cell line interactions in culture

Abstract: Astrocytomas are the most common brain tumors arising in the CNS and account for 65% of all primary brain tumors. Astrocytes have been shown to have the highest predisposition to malignant transformation compared to any other CNS cell type. The majority of astrocytomas are histologically malignant neoplasm. Previous studies have shown that resident astrocytes are the first cell type to react to tumors and surround them. However, the role of these astrocytes in tumor formation and progression has not been deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…This data is consistent with previously published work involving similar co‐culture methods on two‐dimensional surfaces. Whereas these results are consistent with previous work that utilized 2D culture, a number of factors identified as possible causes for the observed GFAP increase were also investigated. Culture of astrocytes with conditioned media from GBM cells and culture with fixed GBM cells presumably displaying surface markers yielded no significant difference in GFAP expression, implying that GBM‐released soluble factors and surface markers contribute minimally, if at all, to astrocytic GFAP response.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This data is consistent with previously published work involving similar co‐culture methods on two‐dimensional surfaces. Whereas these results are consistent with previous work that utilized 2D culture, a number of factors identified as possible causes for the observed GFAP increase were also investigated. Culture of astrocytes with conditioned media from GBM cells and culture with fixed GBM cells presumably displaying surface markers yielded no significant difference in GFAP expression, implying that GBM‐released soluble factors and surface markers contribute minimally, if at all, to astrocytic GFAP response.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, reactive astrogliosis is also evidenced in the presence of glioma and GBM cells in vivo 9 and in vitro. 8,10 Previous work investigating GBMastrocyte interactions has demonstrated that astrocytes upregulate expression of GFAP and matrix metalloproteinase-2 (MMP-2) in the presence of GBM cells 11,12 and has also shown that astrocytes play a supportive role in GBM migration. 13 Thus, in these investigations, we evaluated the relationship between these two well-established characteristics of normal astrocytes and GBM cells, respectively: GFAP expression and cell migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the cell type that characterizes the CNS' response to injury is represented by reactive astrocytes . Importantly, in murine models, non‐neoplastic astrocytes could be converted, by the glioma microenvironment, into a reactive phenotype that could acquire stem cell features similar to GASC . Alternatively, GASC may derive from a recently described population of perivascular mesenchymal stem cells endowed with both mesodermal and neuroectodermal differentiation capacities .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 These compounds appear to underlie pathologic processes and functional disturbances in acute and chronic neurologic disease. 2,[15][16][17] Several cells of the body can produce IL-1, although macrophages are the main source; antioxidants appear to modulate its secretion. 18,19 This cytokine is involved in in ammatory process and is an important stimulator of arachidonic acid metabolism (prostaglandin production).…”
Section: Introductionmentioning
confidence: 99%